Lack of Evidence for Involvement of P-Glycoprotein in Brain Uptake of the Centrally Acting Analgesic, Tramadol in the Rat - Behjat Sheikholeslami; Mehrdad Hamidi; Hoda Lavasani; Mohammad Sharifzadeh; Mohammadreza Rouini (Journal of Pharmacy & Pharmaceutical Sciences, 2012)
Purpose. Tramadol Hydrochloride is a widely-used centrally acting analgesic drug, which has some features of being a P-gp substrate. The present study evaluates the functional involvement of P-gp in CNS distribution of tramadol. Methods. The possibe involvement of P-glycoprotein in brain distribution of tramadol was evaluated using a pharmacokinetic approach in two groups of Pgp-inhibited and control rats. Six male Sprague-Dawley rats were used in each group to collect plasma and brain at 1, 5, 10, and 30 min following two tramadol doses of 1 and 10 mg/kg. Results. The brain uptake clearances of tramadol in Pgp-inhibited and control rats were 2.47±0.56 and 2.34±0.56 ml min-1g-1, respectively, for 1 mg/kg and 3.50±0.60 and 3.14±1.02 mlmin-1g-1, respectively, for 10 mg/kg dose. The brain-to-plasma concentration ratio (Kp,app) of more than 1 in all the time points following both the high and low dose cases (sometimes more than 3) indicated the brain accumulation of the drug. Linear correlation was found between tramadol dose and both corresponding plasma and brain concentrations, but the presence of a dose-dependency was not confirmed by the data obtained for brain-to-plasma concentration ratio. Conclusion. Considering the results of the previous studies and the present research, it seems that the brain accumulation of tramadol is not affected by P-gp inhibition which implies that there may be some other transport mechanisms involved in BBB transport of tramadol.